Eksplorasi Efektivitas Siklus Perencanaan Berkelanjutan dalam Peningkatan Kemampuan Berhitung Siswa Kelas IV di SDN Tumih - Muthoharoh, Tri; Irma; Suhaimi; Sulistiyana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to assess the effectiveness of the PADC (Plan, Do, Check, Act) cycle, adapted from the Kemmis & McTaggart model, in improving the numeracy skills of fourth-grade students at Tumih Elementary School. The background of the problem indicates the low numeracy skills of students in the class and the urgency to find innovative learning approaches. The method used is Classroom Action Research (CAR), involving a series of interventions, observations, and interviews to identify positive shifts. The research findings significantly indicate a substantial improvement in students' numeracy skills. Concrete data shows that the average pre-test score of students was only 30, which then after repeated implementation of the PADC cycle, increased sharply to 70. This 40-point increase demonstrates the effectiveness of the PADC cycle in improving academic performance. Furthermore, the post-intervention condition also showed better material retention and increased student confidence. The conclusion of this study is that the PADC cycle has proven to be a highly effective framework for continuous learning improvement, not only significantly improving numeracy skills in fourth-grade students at Tumih Elementary School but also empowering teachers as adaptive change agents. This approach plays a crucial role in creating a more responsive and effective learning environment tailored to students' needs.